A didactic experience for educating the youngest generations about seismic risk using an escape room - Gargiulo, Maria Vittoria; Napolitano, Ferdinando; Amoroso, Ortensia; Russo, Raffaella; Capuano, Paolo (Frontiers in Communication, 2024)
Effective risk communication is crucial for enhancing societal resilience. It's not just about scientific strategies; it's also about ensuring that communities are informed and prepared. Educating local populations, especially younger generations, is key to improving disaster readiness. Notably, engaging younger generations assumes significance, given their role as both the future of society and conduits for educating their families. Serious Games, specifically Escape Rooms, present a compelling tool for engaging and interacting with young people. These games, designed not primarily for entertainment but for educational purposes, facilitate active participant involvement, thereby enhancing learning. In our didactic approach, comprising a frontal lesson and an Escape Room, we sought to leverage the appeal of Serious Games to educate young people. This approach was particularly timely during the COVID-19 pandemic, where virtual experiences gained positive evaluations despite the inherent challenges. Italy frequently faces large magnitude earthquakes. Yet many Italians, especially young people, have low seismic risk awareness, hindering preparedness efforts. To address this issue, the use of games and interactive experiences proves promising. By involving young people, seismic risk awareness can be effectively raised, fostering a culture of safety. Throughout the implementation of the Escape Room exercise dedicated to seismic risk, we conducted an evaluation phase both before and after the activities. The insights gained from this evaluation process provided valuable feedback on the learning experience and the effectiveness of the science communication technique. Notably, the virtual nature of the escape room experience was positively evaluated, demonstrating its adaptability during the pandemic. It is imperative to acknowledge that participants in these activities were aged between 15-18 years old, requiring ethical considerations in the design and execution of the educational intervention. The findings are highly promising, indicating that students viewed the protocol as beneficial for understanding fundamental concepts in seismology and enhancing their perception of risk. Moreover, the protocol positively influenced students' interest in science and geophysics. Furthermore, an aspect that remains unexplored is the extent to which the knowledge acquired by the participants was disseminated within their families, representing a potential area for future investigation.